1997
DOI: 10.1105/tpc.9.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Modification of seed oil content and acyl composition in the brassicaceae by expression of a yeast sn-2 acyltransferase gene.

Abstract: A putative yeast sn-2 acyltransferase gene (SLC7-7), reportedly a variant acyltransferase that suppresses a genetic defect in sphingolipid long-chain base biosynthesis, has been expressed in a yeast SLC deletion strain. The SLC7-7 gene product was shown in vitro to encode an sn-2 acyltransferase capable of acylating sn-1 oleoyl-lysophosphatidic acid, using a range of acyl-COA thioesters, including 181-, 22:l-, and 240-COAS. The SLC7-7 gene was introduced into Arabidopsis and a high erucic acid-containing Brass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
168
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 275 publications
(177 citation statements)
references
References 34 publications
(28 reference statements)
8
168
0
1
Order By: Relevance
“…These findings, as well as the increase in the oil content, highlight the effect of the yeast LPAAT which allows an increase in the flow of fatty acids in the triglycerides biosynthetic pathway. The use of acyl-CoA thioesters by all acyltransferases involved in the biosynthesis of triglycerides seems to stimulate the biosynthesis of VLCFAs probably by removing feedback inhibition (Frentzen, 1998;Zou et al, 1997). The results obtained with the yeast LPAAT should be attributed to the specific properties of this enzyme.…”
Section: The Lysophospatidic Acid Acyltransferase (Lpaat)mentioning
confidence: 87%
See 4 more Smart Citations
“…These findings, as well as the increase in the oil content, highlight the effect of the yeast LPAAT which allows an increase in the flow of fatty acids in the triglycerides biosynthetic pathway. The use of acyl-CoA thioesters by all acyltransferases involved in the biosynthesis of triglycerides seems to stimulate the biosynthesis of VLCFAs probably by removing feedback inhibition (Frentzen, 1998;Zou et al, 1997). The results obtained with the yeast LPAAT should be attributed to the specific properties of this enzyme.…”
Section: The Lysophospatidic Acid Acyltransferase (Lpaat)mentioning
confidence: 87%
“…However, the overall proportions of 22:1 in the seed oil did not increase. Zou et al (1997) have confirmed that the yeast (Saccharomyces cerevisiae) SLC1-1 gene encodes sn-2-acyltransferase capable of acylating sn-1-oleoyl-lysophosphatidic acid using a range of acyl-CoA thioesters, including 22:1-CoA. However, neither the meadowfoam nor the yeast-LPAAT transgene approach was successful in achieving high trierucin content in HEAR B. napus seed oil.…”
Section: The Lysophospatidic Acid Acyltransferase (Lpaat)mentioning
confidence: 88%
See 3 more Smart Citations